Tumour necrosis factor‐α plays a significant role in the Aldara‐induced skin inflammation in mice. (1st May 2016) - Vinter, H.; Kragballe, K.; Steiniche, T.; Gaestel, M.; Iversen, L.; Johansen, C.
Summary: Background: Recently, the Aldara‐induced psoriasis‐like skin inflammation model in mice has attracted increased attention, due to its dependence on the same immunological pathways and cell types as in human psoriasis. Objectives: To study the impact of constitutive deficiency of tumour necrosis factor (TNF)‐α and its upstream regulator mitogen‐activated protein kinase‐activated protein kinase 2 (MAPKAPK‐2, herein MK2) in the Aldara‐induced psoriasis‐like skin inflammation model. Methods: TNF‐α knockout (KO), MK2 KO and wild‐type (WT) mice divided into separate groups received either 45‐mg Aldara cream or control cream for 5 consecutive days. The skin inflammation was evaluated clinically, histologically, and by quantitative reverse transcription‐polymerase chain reaction. Results: We found that TNF‐α KO mice developed significantly less skin inflammation compared with WT mice, as evaluated clinically and histologically. At the molecular level, we demonstrated that the Aldara‐induced mRNA expression of the psoriasis‐related inflammatory markers interleukin (IL)‐17C, IL‐23p19, IL‐12p40, IL‐17A, IL‐22 and S100A8 was significantly decreased in TNF‐α KO mice compared with WT mice. No significant difference in the mRNA expression of these inflammatory markers between MK2 KO mice and WT mice was found, although Aldara‐treated MK2 KO mice showed a tendency towards a lower mRNA expression of IL‐17A and IL‐22 compared with WT mice. Conclusions: We were able to demonstrate significantly lower levels of inflammation in TNF‐α KO mice compared with WT mice, supporting the use of this model in future studies characterizing the role of TNF‐α in psoriasis.